2018
DOI: 10.1002/jcb.27326
|View full text |Cite
|
Sign up to set email alerts
|

Decreased miR‐200a‐3p is a key regulator of renal carcinoma growth and migration by directly targeting CBL

Abstract: Although emerging evidence has revealed that microRNAs (miRNAs) dysregulation contribute to carcinogenesis, the mechanism underlying their roles in renal cell carcinoma (RCC) is unclear. The purpose of the current study was to analyze the association of miR-200a-3p expression with RCC and to understand potential novel target genes, functions and mechanisms of miR-200a-3p in RCC. MiR-200a-3p expression levels were first measured by quantitative real-time polymerase chain reaction and in situ hybridization in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…MicroRNAs (miRNA) have been investigated to participate in the pathological process of many diseases by regulating cell metabolism, proliferation, migration, apoptosis, and drug resistance [ 26 , 27 ]. MiR-200a-3p is a functional miRNA and has been demonstrated to inhibit cell tumorigenesis in many types of cancers, such as papillary thyroid carcinoma [ 28 ], gastric cancer [ 29 ], renal cancer [ 30 ], and so on. In addition, miR-200a-3p also was implied to involve in the regulation of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNA) have been investigated to participate in the pathological process of many diseases by regulating cell metabolism, proliferation, migration, apoptosis, and drug resistance [ 26 , 27 ]. MiR-200a-3p is a functional miRNA and has been demonstrated to inhibit cell tumorigenesis in many types of cancers, such as papillary thyroid carcinoma [ 28 ], gastric cancer [ 29 ], renal cancer [ 30 ], and so on. In addition, miR-200a-3p also was implied to involve in the regulation of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer (GC) tissues, miR-200a-3p plays a cancer suppressing role in GC by targeting KLF12 [26]. In renal cell carcinoma (RCC), the miR-200a-3p/CBL regulatory axis is a new mechanism under pathogenesis [27]. After using high-throughput sequencing to analyze the ovarian tissues of chickens with lower and higher egg rates, Wu et al found that miR-200a-3p may play a special central role in the reproductive regulation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the miR-125 family, which potentially acts as tumor suppressors has been reported in different types of cancer, including cutaneous melanoma [46,47]. Likewise, miR-200a-3p (renal carcinoma, pancreatic cancer), miR-423-5p (gastric cancer), miR-31-5p(Oral Cancer), miR-141-3p (rectal cancer) and miR-140-3p.1 (breast cancer) have also been implicated in different types of cancer [48,49,50,51,52,53]. Based on our study, we have observed that the regulatory network associated with BAP1-miRNAs is unique in comparison to the common miRNAs regulatory network in UM.…”
Section: Discussionmentioning
confidence: 99%